Deconstructing Intentionality: Legal Fallacies in The Indonesian Criminal Code's Approach to Mens Rea - Ramadan, Tubagus Ahmad; Mandala, Subianta (Asian Journal of Social and Humanities, 2025)
This study examines the interpretative fallacies surrounding mens rea in Indonesia’s criminal justice system. Disparities in the interpretation of intentionality (opzet) by law enforcement officials and judges often result in significant inconsistencies in legal outcomes. Using a qualitative library research method with legal hermeneutics and critical discourse analysis, this study investigates 150 court decisions from 2020 to 2023 to identify structural and cultural causes of these inconsistencies. The findings reveal that 68% of verdicts contained ambiguity in the construction of mens rea, mainly due to outdated legal frameworks, limited interdisciplinary education, and external pressures. To address this, the study proposes an interdisciplinary reconstruction of the concept of intentionality that integrates insights from cognitive psychology with criminal law doctrine. This includes the development of a nuanced intentionality spectrum and practical tools such as the Intentionality Assessment Protocol (IAP). The findings highlight the complexity of mens rea interpretations within the Indonesian legal system, with substantial variations in judicial decisions. The study proposes a new conceptual framework based on cognitive psychology to bridge gaps in understanding intentionality. Further recommendations for reform include the development of legal education and training systems for law enforcement.